Knowledge, Attitudes, and Behavior of High School Students in Banjarmasin Towards Water Resources and Pollution - Yusup, Febrianawati (Universitas Sembilanbelas November Kolaka, 2024)
The rivers in Banjarmasin are polluted due to people's behavior. Changing behavior to be more positive towards the environment can be done through environmental education that can be integrated into the high school curriculum. High school students in Banjarmasin City are very appropriate to study their attitudes, knowledge, and behavior towards the environment, especially water resources and pollution because they are considered agents of change and their changes are an important sign of long-term social change. This study aims to describe the attitudes, knowledge, and behavior of high school students in Banjarmasin towards water resources and pollution. This study used descriptive survey research. The sample in this study was 236 students selected using two-stage random sampling from a population of all high school students in Banjarmasin City, South Kalimantan. Students' knowledge about water resources and pollution was explored using tests, while students' attitudes and behaviors were explored using non-tests, all of which were analyzed descriptively quantitatively. The average score of students' knowledge about water resources and pollution reached 56%, which is included in the medium criteria. The average value of students' attitudes towards water resources and pollution reached 71% which is included in the positive criteria. The average value of student behavior towards water resources and pollution reached 67%, including medium criteria. However, it is still necessary to continuously improve the knowledge, attitudes, and behaviors of secondary school students to be more positive and better.